A configuração da profissão de secretário em Sergipe : educação, atuação e organização da área (1975-2010) - Sabino, Rosimeri Ferraz (2017)
This thesis is aimed at researching the configuration of the secretarial profession in the State of Sergipe, from 1975 to 2010, seeking to understand the processes in which education, labor market space and organization of these professionals occurred in their representing entities. An historical research was conducted using the elements of Cultural History. The main categories analyzed were the concepts of “figuration, configuration and interdependency” of Norbert Elias, “field, capital and habitus”, of Pierre Bourdieu, and “ownership and representation” of Roger Chartier. The time period of this research uses Decree no 20.158 of 1931, as an antecedent reference that estalished Comercial Education in Brazil, which included the secretarial technical course. However, the occupation was just legalized in 1978, and thus became a regulated profession, with specialized education for those interested in following this path. In Sergipe, the first training courses for secretaries came to be in 1975. In the following years, the secretarial technical courses were created, Tobias Barreto College, Aracaju, as the first in 1976, Diocesano College, Propriá in 1980 and Serviço Nacional de Aprendizagem Comercial, Aracaju, in 1996. Tiradentes University started the graduation course in the year 1989 and cancelled it the year 2000, and the Federal University of Sergipe started the course in 2006 and continues till date. Thus, the trajectory of education spaces, insertion and action of these professionals in the labor market were analyzed until the year 2010, which was the graduation year of the first class of secretarial studies from the Federal University of Sergipe. The study showed that, though under legal protection and collective representation, the systematization of knowledge for the practice of future secretaries, through specific courses, was not a sufficient movement to give the occupation the status of “profession”. Unable to express its relevance to society, education for the secretaries contributed to its configuration as “passing professionalization”. This thesis is defended under the confirmation that the education provided allows students to complete a given level of education, but not entry into a job field related to the title obtained. The specialized education being the main element of the delimitation of the field, did not receive distinction before social practices, thus remains confronted with historically constituted meanings about secretarial activities.